Catumiri Guadanucci, 2004: New diagnosis, first description of the female of C. petropolium Guadanucci, 2004, and new records of the genus from Brazil and Uruguay (Theraphosidae: Ischnocolinae) - Galleti-Lima, Arthur [UNESP]; Indicatti, Rafael Prezzi [UNESP]; Guadanucci, José Paulo Leite [UNESP] (Arachology, 2021)
The ischnocoline genus CatumiriGuadanucci, 2004 comprises four species distributed in Argentina, Brazil, Chile, and Uruguay. The type species Catumiri petropoliumGuadanucci, 2004 is known only from the male. We here provide a new diagnosis for Catumiri, describe the female of C. petropolium, and report new records of this species from Parque Nacional da Serra dos Órgãos, Reserva Biológica do Tinguá and Parque Nacional da Serra da Bocaina, Rio de Janeiro, Brazil. We also expand the distribution of Catumiri parvum (Keyserling, 1878) to Parque Nacional de Aparados da Serra, Praia Grande, Santa Catarina, Brazil, Alegrete, Rosário do Sul, Santana do Livramento, Pinheiro Machado, Bagé, and Jaguarão, all from Rio Grande do Sul, Brazil and Cerro de Los Cuervos, Lavalleja, Uruguay.
Keywords: Atlantic Forest; Mygalomorphae; tarantula; taxonomy